Simultaneous precipitation and discharge plasma processing for one-step synthesis of α-Fe2O3–Fe3O4/graphene visible light magnetically separable photocatalysts. Issue 11 (7th March 2023) - Tuyen, Nguyen Long; Toan, Tran Quoc; Hung, Nguyen Ba; Trieu, Pham Quoc; Dinh, Nguyen Ngoc; Do, Danh Bich; Van Thanh, Dang; Nguyen, Van-Truong
Abstract : A novel facile combination of precipitation and plasma discharge reaction is successfully employed for one-step synthesis of an α-Fe2 O3 –Fe3 O4 graphene nanocomposite (GFs). Abstract : A novel facile combination of precipitation and plasma discharge reaction is successfully employed for one-step synthesis of an α-Fe2 O3 –Fe3 O4 graphene nanocomposite (GFs). The co-existence and anchoring of hematite (α-Fe2 O3 ) and magnetite (Fe3 O4 ) nanoparticles onto a graphene sheet in the as synthesized GFs were verified by results of XRD, Raman, SEM, TEM, and XPS. HRTEM characterization was used for confirming the bonding between α-Fe2 O3 /Fe3 O4 nanoparticles and the graphene sheet. Consequently, GFs shows superior photodegrading performance towards methylene blue (MB), compared to individual α-Fe2 O3 /Fe3 O4 nanoparticles, as a result of band gap narrowing and the electron–hole pair recombination rate reducing. Moreover, GFs allows a good possibility of separating and recycling under an external-magnetic field, suggesting potential in visible-light-promoted photocatalytic applications.